E46K α-Synuclein Mutation Fails to Promote Neurite Outgrowth by Not Inducing Cdc42EP2 Expression, Unlike Wild-Type or A53T α-Synuclein in SK-N-SH Cells - Hyunja Jung; Seonghan Kim (Brain Sciences)
Background/Objectives: α-Synuclein (α-syn) protein is a major pathological agent of familial Parkinson’s disease (PD), and its levels and aggregations determine neurotoxicity in PD pathogenesis. Although the pathophysiological functions of α-syn have been extensively studied, its biological functions remain elusive, and there are reports of wild-type (WT) α-syn and two missense mutations of α-syn (A30P and A53T) inducing protective neuritogenesis through neurite outgrowth. However, the function of another α-syn mutation, E46K, has not been fully elucidated. Thus, we compared the effect of E46K α-syn with other types to identify the mechanisms underlying neurite outgrowth. Methods: We transfected SK-N-SH cells with WT and mutant (A53T and E46K) α-syn to investigate the effects of their overexpression on neurite outgrowth. Then, we compared the differential effects of α-syn on neurite outgrowth using microscopic analysis, including confocal microscopy. We also analyzed the differential regulation of cell division control 42 effector protein 2 (Cdc42EP2) using real-time quantitative polymerase chain reaction and western blot analysis. Finally, to confirm the implication of neurite outgrowth, we knocked down Cdc42EP2 using small interfering RNA. Results: Unlike WT and A53T α-syn, E46K α-syn failed to promote neurite outgrowth by not inducing Cdc42EP2 and subsequent βIII-tubulin expression. Cdc42EP2 knockdown impaired neurite outgrowth in WT and A53T α-syn transfectants. Conclusions: Our findings suggest that WT and mutant α-syn are linked to Cdc42EP2 production in neuritogenesis, implying α-syn involvement in the physiological function of axon growth and synapse formation. Thus, α-syn may be a potential therapeutic target for PD.